Hemodialysis Access Choice: Impact of Health Literacy - Andrea Mazarova; Swapnil Hiremath; Manish M. Sood; Edward G. Clark; Pierre Antoine Brown; Ann L. Bugeja; Grant L. England; Deborah Zimmerman (SLACK Incorporated, 2017)
Background: Hemodialysis patients need to make decisions about vascular access and diet that they may not fully understand. In this study, we hypothesized that patients with low health literacy are likely to choose a central venous catheter (CVC) and have higher serum potassium (K), serum phosphate (P), and inter-dialysis weight gains (IDWG). Objective: Primarily, the study sought to describe the health literacy of patients treated with hemodialysis in a Canadian tertiary care center. The secondary objective was to describe the association between health literacy and permanent vascular access choice, hyperkalemia, hyperphosphatemia, and IDWG. Methods: Adult patients receiving hemodialysis for more than 6 months were included. Health literacy was assessed with the Newest Vital Sign (NVS) test. Vascular access type and reasons for CVC use were determined. Serum K, P, and IDWG were collected retrospectively for 6 months. Student's t test and logistic regression were used to determine the association between health literacy (NVS score < 4 versus ≥ 4) and CVC choice, hyperkalemia, hyperphosphatemia, and high IDWG. Key Results: Fifty-six patients were involved. The average NVS score was 2.9. Overall, 66% of the patients had a CVC; one-third had chosen this access themselves. Poor control of K, P, and IDWG was experienced by 27%, 55%, and 36% of patients, respectively. The average NVS score was lower for patients choosing a CVC (p = .001), but not different for those with higher K, P, or IDWG. None of the patients who chose a CVC had adequate health literacy (NVS ≥ 4). Conclusions: Patients with low health literacy, who are eligible for both surgically created vascular access (fistula or graft) and CVC, are more likely to refuse fistula/graft creation compared to patients with adequate health literacy. Different educational strategies for such patients may help in appropriate decision-making.